The Impact of Anti-Money Politics Movement at Murtigading Village in 2019 Concurrent Elections - Moch Edward Trias Pahlevi; Bambang Eka Cahya Widodo; Rio Kalpiando; Fairuz Arta Abhipraya; Azka Abdi Amrurobbi (Journal of Local Government Issues (LOGOS), 2020)
The Indonesian elections still face money politic practices as one of the electoral issues. This political transactional transforms into a new typical behavior and even becomes a culture for Indonesian citizen in every election. This lousy culture currently became the significant factor in gaining a victory for candidates, such as for 2019 concurrent election. Money politic practices are not only harmful to electoral integrity but also has a long-term impact on a new behavior to produce corruptors. This study seeks to examine the evaluation and impact of Anti-Money Politic Village movement in Murtigading Village, Bantul Regency, Special Region of Yogyakarta for 2019 concurrent election. This study used a quantitative method. The primary source for this study was obtained from survey techniques. This study leads to the three main conclusions such as: first, Murtigading community considers money politics as a form of bribery action and potentially harmful for democracy value. Second, Murtigading community considers that movement can decrease the practice of money politics in Murtigading village. Third, Murtigading community fully supports the existence of that movement and support to establish the legal regulations in local village government to create more political education among the community quickly